Isolation of diverse members of the Aquificales from geothermal springs in Tengchong, China - Hedlund, Brian P.; Reysenbach, Anna-Louise; Huang, Liuquin; Ong, John C.; Liu, Zizhang; Dodsworth, Jeremy A.; Ahmed, Reham; Williams, Amanda J.; Briggs, Brandon R.; Liu, Yitai; Hou, Weiguo; Dong, Hailiang (Frontiers in Microbiology, 2015)
The order Aquificales (phylum Aquificae) consists of thermophilic and hyperthermophilic bacteria that are prominent in many geothermal systems, including those in Tengchong, Yunnan Province, China. However, Aquificales have not previously been isolated from Tengchong. We isolated five strains of Aquificales from diverse springs (temperature 60.0-82.9°C and pH 2.6-8.9) in the Rehai Geothermal Field from sites in which Aquificales were abundant. Phylogenetic analysis showed that four of the strains belong to the genera Hydrogenobacter, Hydrogenobaculum, and Sulfurihydrogenibium, including strains distant enough to likely justify new species of Hydrogenobacter and Hydrogenobaculum. The additional strain may represent a new genus in the Hydrogenothermaceae. All strains were capable of aerobic respiration under microaerophilic conditions; however, they had variable capacity for chemolithotrophic oxidation of hydrogen and sulfur compounds and nitrate reduction.